Role of mGlu7 receptor in morphine rewarding effects is uncovered by a novel orthosteric agonist. (15th March 2018) - Hajasova, Zuzana; Canestrelli, Corinne; Acher, Francine; Noble, Florence; Marie, Nicolas
Abstract: Opiate dependence is a major health issue and despite the existence of opioid substitution treatment, relapse frequently occurs. Group III metabotropic glutamate (mGlu) receptors has received much attention as a putative target in ethanol and cocaine addiction, but no data on opiate addiction exist. So we investigated the role of group III mGlu receptors in morphine rewarding effects through the expression and the reinstatement of conditioned place preference (CPP) using a newly synthesized mGlu4/mGlu7 receptor orthosteric agonist, LSP2-9166. We found that LSP2-9166 blocked morphine CPP expression and reinstatement after extinction. Blockade of CPP expression with LSP2-9166 was abolished when using XAP044, a mGlu7 antagonist. We also found that LSP2-9166 at the dose active for blocking morphine reward was devoid of any effect on locomotion, hedonic state, spatial memory, anxiety or depression. Altogether our data demonstrated that group III mGlu receptors, and more specifically mGlu7, might be a valuable target in opiate addiction. Highlights: LSP2-9166 blocks expression of morphine reward. LSP2-9166 inhibits reinstatement of morphine-conditioned reward after extinction. Effects of LSP2-9166 on morphine reward depends on mGlu7 receptors.